PKM Mothers Empowerment Residents Of West Labuh Baru Village Becoming A Homemade Yoghurt Businessman - Joesyiana, Kiki; Wahyuni, Sri; Yuzalmi, Nanik; Basriani, Agustin; Susanti, Desi; Harahap, Arief Rifa’i (Doctoral Program of Social Science, Pasundan University, 2024)
Empowering mothers of Labuh Baru Barat sub-district residents is very important, because it aims to foster awareness and independence in entrepreneurship, as well as expand employment opportunities to increase family income in an effort to achieve community welfare. This activity is expected to increase the skills of mothers of Labuh Baru Barat sub-district residents in processing fresh cow's milk which is processed with flavored syrup extract into functional food products that have health benefits and high selling value, namely synbiotic yogurt which is good for gut health. The mothers of Labuh Baru Barat residents feel that at this time they must participate in thinking about how to improve their abilities and creativity in entrepreneurship in order to help restore the economic conditions of households after the Covid-19 pandemic, the impact of which is still being felt today. After carrying out monitoring activities, it was seen that what was needed by the mothers of Labuh Baru Barat residents was to increase their knowledge and skills in creating products that had good selling power in today's society. Due to the above problems, we as a team of lecturers from the Management Study Program of the College of Economics carried out community service activities that were oriented towards empowering mothers of West Labuh Baru residents in improving their ability to produce products so that they can be resold so that they can help increase household income with the theme